Unlocking Sports Tourism Potential in Pangkep Regency through Strategic Development and Community Engagement - Nur Alim; Muh. Adnan Hudain; Jamaluddin Jamaluddin; Arifuddin Usman; Syahruddin Syahruddin (Journal La Bisecoman, 2024)
This research aims to assess the posibility of developing sports tourism in weather diverse and culturally enchanted Pangkep Regency which faces critical issues of infrastructure and strategies necessary in the field. The study aims at identifying how the physical environment of Pangkep including mountains for hiking and cliff activities, as well as islands for snorkeling and diving can be used to build up the emerging sports tourism market. Also, it focuses on exploring the possible roles and potentials of the Mappasoro Kappala ritual when including into the organisation of tourism activities. But the study shows strengths which have hampered these potentialities such as poor infrastructure, poor marketing and poor community participation. The absence of infrastructure and safety provisions as well as a coordinated regional approach to tourism development limits the region’s opportunity to develop and package a reliable whole year round tourist product. Furthermore, the fact is that local communities are ready to participate in the development of tourism, but there is a significant lack of information and materials that would allow them to have meaningful participation. In response to these challenges, therefore, the study provides several recommendations that include; Developing sustainable infrastructure to support the future growth of the program, strengthening the capacities of the community to increase their active participation in related programs, and formed a composited task force of some stakeholders to enhance coordination at the strategic level. Marketing promotion made to both domestic and foreign tourists is required in the market promotion unique products and assets.